Kuolleet omenapuut: Runollista proosaa - Lehtonen, Joel, 1881-1934 (Salt Lake City, UT : Project Gutenberg, 2005)
"Kuolleet omenapuut: Runollista proosaa" by Joel Lehtonen is a collection of poetic prose written in the early 20th century. The text appears to explore themes of contentment, nature, and the simplicity of rural life through its central character, Aapeli Muttinen, who seeks solace from the hectic urban existence by returning to his idyllic countryside villa during the summer months. The opening of the work introduces Aapeli Muttinen, a bookshop owner, as he reflects on the pleasures of summer and the peace that nature brings after a long winter. Muttinen, feeling exhausted from city life, finds joy in the beauty of the spring season and the presence of Lyygia, a character who represents his companion and counterpart. As they indulge in simple pleasures such as eating freshly caught fish and exploring their surroundings, the narrative paints a vivid picture of a tranquil, nostalgic summer filled with fleeting happy moments, contrasting with the eventual recognition of life's transience and the deeper melancholy it brings. (This is an automatically generated summary.)
Release date is 2005-09-17
Produced by Matti Järvinen, Tuija Lindholm and Distributed Proofreaders Europe
Keywords: Finnish fiction